Antimalarial activity of Neopetrosia exigua extract in mice - Abdillah, Syamsudin; Ahmad, Rahmatul Wahidah; Muzaki, Farid Kamal; Mohd Noor, Noriah (Association of Pharmaceutical Innovators, 2013)
Objective: To evaluate the antimalarial activity of ethanolic extract of Neopetrosia exigua in ICR mice. The safety of the extracts was also ICR mice by the acute oral toxicity test. Methods: The crude ethanol extract of Neopetrosia exigua (50, 100, 200 and 400 mg/kg) was investigated for its antimalarial activity against Plasmodium berghei during early infection. The acute toxicity of the extract was also investigated. At the end of 14 days, mice were sacrificed for histopathology study. Results: The extract of Neopetrosia exigua demonstrated significant ( p <0.05) schizonticidal activity. The acute toxicity test showed that the extract of Neopetrosia exigua is toxicological safe by oral administration. Histopathological study revealed normal architecture of kidney and liver of mice.